Does bilateral superficial cervical plexus block decrease analgesic requirement after thyroid surgery? - GÜLLÜOĞLU, MAHMUT BAHADIR (LIPPINCOTT WILLIAMS & WILKINS, 2006)
In this randomized, double-blind and controlled study we evaluated and compared the analgesic efficacy of bilateral superficial cervical plexus block and local anesthetic wound infiltration after thyroid surgery. Forty-five patients were assigned to 3 groups. After general anesthesia induction, bilateral superficial cervical plexus block with 0.25% bupivacaine 15 mL in each side was performed in Group 1, and local anesthetic wound infiltration with 0.25% bupivacaine 20 mL was performed in Group H. In Group III (control) no regional block was administered. Intravenous patient-controlled analgesia was used to evaluate postoperative analgesic requirement. Neither visual analog scale scores nor total patient-controlled analgesia doses were different among groups. We concluded that bilateral superficial cervical plexus block or local anesthetic wound infiltration with 0.25% bupivacaine did not decrease analgesic requirement after thyroid surgery.
Keywords: POSTOPERATIVE PAIN RELIEF; WOUND INFILTRATION; ANESTHESIA; BUPIVACAINE